Die maatskaplike impukasies en impak van VIGS: ’n Verkenning - Weyers, M. L. (Koers, 1990)
In this paper it is mainly postulated that the reaction of South African society to HIV infections and AIDS will follow the same basic process as that encountered by the infected individual. Should the process be made applicable to the existing projections, it will imply the following: South Africa al present finds itself in the first phase of denial and escalating fear. As from approximately 1995, when HIV infections will increase dramatically, a phase of disillusionment and emotional disorganisation should set in. During the period 1999 to 2003 the confirmed cases of AIDS will reach a zenith. As a result, phases three and four, comprising role changes and acceptance or anger, will follow one another in rapid succession. The fifth phase, which in the case of the individual is death, is indefinable in terms of social reaction. Measured against society’s reactions to pandemics in the past, a phase of reconstruction should commence by 2006. The primary unknown factor which will influence the course of the process, is what South African society's dominant perceptions of AIDS will be as the process unfolds.